Secondary Porosity Development in Bangladeshi Gas Reservoirs: A Case Study of the Fenchuganj Gas Field (Well no: 2) (The Dhaka University Journal of Earth and Environmental Sciences, 2023)
The Fenchuganj gas field is located in Surma basin and is uniform throughout the whole southern area. This study deals with the development of secondary porosity of the gas bearing reservoir sandstone rocks with the microscopic analysis of the core sample rock slides from well 2 of Fenchuganj gas field. The study shows the secondary porosity was generated at the particular depths of 1479-1497 m, 2768-2783 m and 3615-3624 m of Fenchuganj well no.2. The study demonstrates that diagenetic parameters, such as compaction, pressure solution, and cementation, are not the only ones that affect reservoir quality. Other elements include the reservoir rock's chemical environment, acidic water infiltration or dissolution, the presence of any other secondary processes, etc.Acidic water intrusion may have acted as an agent in generation of these secondary porosities. On contrast, the rocks in 2190 m, 3424-3432 m and rest of 3615-3624 m depth, had lost its porosity by the adverse effects of compaction, cementation as well as pore pressure solution. The overall porosity of the rock samples F-2 (1479–1497 m), F-6 (2768–2783 m), and F-10b (3615–3624 m) is around (35–40%), (30–35%), and (20–25%), respectively, indicating excellent, very good, and good reservoir quality for rock slide F-2, F-6, and F-10b, respectively. Changing of chemical environment and consequent dissolution process may contribute to enhance the potentiality of reservoir rock.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 11(1), 2022, P 43-52